2015
DOI: 10.1071/bt14242
|View full text |Cite
|
Sign up to set email alerts
|

Metal accumulation by Arabidopsis halleri subsp. gemmifera at a limestone mining site

Abstract: Arabidopsis halleri subsp. gemmifera, a close wild relative of A. thaliana in eastern Asia, is an important model species of Brassicaceae used to study cadmium (Cd) and zinc (Zn) tolerance and hyperaccumulation in plants. To investigate the effects of soil factors on metal accumulation in this plant, we collected plants and rhizosphere soil samples from a limestone mining site on Mount Ibuki, and compared them with those collected from non-calcareous soil in Japan. Irrespective of the sampling site, all the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It has been previously reported that naturally growing plants at high altitude on Mt. Ibuki accumulated less zinc than plants growing in non-calcareous habitats at lower altitudes (Kosugi et al 2015).…”
Section: Studies On Population Differentiation and Local Adaptationmentioning
confidence: 97%
“…It has been previously reported that naturally growing plants at high altitude on Mt. Ibuki accumulated less zinc than plants growing in non-calcareous habitats at lower altitudes (Kosugi et al 2015).…”
Section: Studies On Population Differentiation and Local Adaptationmentioning
confidence: 97%
“…These satellites include Cardamine hirsuta for compound leaf development (Hay et al, 2014; Bar and Ori, 2015), Arabidopsis halleri , a cadmium and zinc hyperaccumulating plant (Kubota et al, 2015; Kosugi et al, 2015), Boechera species that exhibit apomixis (asexual reproduction) (Rushworth et al, 2011), and Arabis alpina , a model for the ecology of alpine and arctic environments that has a perennial rather than annual life cycle (Wang et al, 2009). Some A. alpina populations are self-fertilizing, while others appear to manifest sporophytic self-incompatibility (Tedder et al, 2011).…”
Section: Diversification In Eudicotsmentioning
confidence: 99%
“…Although studies generally focus on the effects of a single stress factor, these stress factors are likely to have combined effects (Von Wettberg et al 2014), as in the case for Ca : Mg ratio and water availability on traits of Mimulus guttatus (Phrymaceae, Murren et al 2006;Selby et al 2014). Presentations also focussed on elemental uptake and localisation in tissues of plants tolerant of ultramafic and other chemically imbalanced soils (Kosugi et al 2015;Mizuno and Kirihata 2015;Pavlova et al 2015), including the use of advanced techniques such as micro-PIXE in mapping regions of elemental concentration within plant tissue (Przybyłowicz et al 2005(Przybyłowicz et al , 2014. Tolerance of high concentrations of heavy metals, including molecular mechanisms underlying metal tolerance, has also received attention (Janssens et al 2009;Gall and Rajakaruna 2013;Viehweger 2014).…”
Section: Physiology and Evolution (Session 4)mentioning
confidence: 99%